Sustainable performance evaluation of pharmaceutical companies: sustainable balanced scorecard and hybrid MCDM approach - Deng, Deqiang; Zhang, Jiayang; Wang, Jingyi; Zong, Xiuran (Frontiers in Public Health, 2025)
Despite the increasing demand for sustainable development of pharmaceutical companies due to the rigorous pressure of environmental regulation, public health crisis and economic competition, there has been little research on relevant evaluation models. The COVID-19 experience has also prompted investors in pharmaceutical companies to re-examine the impact of environment and ethics on business development. Therefore, pharmaceutical companies need to focus on their performance, especially on the shift from a single financial performance to an integrated performance. This paper constructs a reticulated sustainable performance evaluation model for decision-makers based on the Sustainability Balanced Scorecard (SBSC) framework. The evaluation results are derived using Decision Making Experiment and Evaluation Laboratory (DEMATEL), Analytical Network Process (ANP) and modified VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR). The model can help management gain a more comprehensive understanding of the company’s overall situation, promote management’s focus on the balance and synergies between the various dimensions and indicators of sustainability performance, clarify the relationships and the comment weights of evaluation dimensions and indicators, and provide sustainability improvement solutions, which have been neglected in previous research on the evaluation of sustainability performance of pharmaceutical companies. Based on questionnaires with experts, this paper finds that the Environment is the most important factor, followed by Internal Processes, Customers, Finance, Learning and Growth, as well as Society. The empirical results of a Chinese pharmaceutical company suggest that green transformation and customer relations are the priorities, in addition to the need for additional ways to improve the sustainability performance of pharmaceutical companies. The evaluation results provide a strategic reference for stakeholders, which helps the case company to find better strategies for sustainable development and priorities for improving their sustainability performance.